FLUORIDE OCCURRENCE IN PUBLICLY SUPPLIED DRINKING WATER IN ESTONIA - Karro E.; Indermitte E.; Saava A.; Haamer K.; Marandi A. (My University, 2006)
A study was undertaken to examine the content and spatial distribution of fluoride in drinking water. Water samples (735) from public water systems covering all Estonian territory were analysed using SPADNS method. In order to specify the natural source of fluoride, the chemistry data from five aquifer systems utilised for water supply were included into the study. Fluoride concentrations in tap water, to a great extent, ranged from 0.01 to 6.95 mg/l. Drinking water in southern Estonia, where terrigenous Middle-Devonian aquifer system is exploited, has a fluoride concentration lower than recommended level (0.5 mg/l), thus promoting susceptibility to dental caries. The western part of the country is supplied by water with excess fluoride content (1.5–6.9 mg/l). Groundwater abstracted for drinking purposes originates from Ordovician and Silurian carbonate rocks. The content of fluoride in Silurian–Ordovician aquifer system is associated with the groundwater abstraction depth and the main controlling factors of dissolved fluoride are the pH value and the chemical type of water.
Keywords: DRINKING WATER; FLUORIDE; GROUNDWATER; ESTONIA; Палеозой::Девонская; Палеозой::Силурийская; Палеозой::Ордовикская; Paleozoic::Devonian; Paleozoic::Silurian; Paleozoic::Ordovician